2014
DOI: 10.1007/s00334-014-0459-x
|View full text |Cite
|
Sign up to set email alerts
|

The potential of micromorphology for interpreting sedimentation processes in wetland sites: a case study of a Late Bronze–early Iron Age lakeshore settlement at Lake Luokesa (Lithuania)

Abstract: Lake Luokesa lies in the eastern part of Lithuania and is part of a region of lakes formed by the Scandinavian ice-sheet and its melt waters during the last glaciation. During the Late Bronze-Early Iron Age transition, between 625 and 535 cal BC, a lakeside settlement with an onshore palisade was built on the platform of a carbonate bank. A total of five profiles, each comprising an organic occupation layer and lake sediments at its bottom and top, were examined micromorphologically. In this paper, natural and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 38 publications
1
14
0
1
Order By: Relevance
“…4A), with single fine charcoal fragments. It may represent the natural accumulation of organic material in the transition zone between the lake and land, but anthropogenic settlement activities, too, should be taken into account as a primary forming factor, as in the case of similar contexts (albeit with more numerous and differentiated anthropogenic inclusions) investigated at Lake Luokesa (Lithuania) and several Swiss lakeshore sites (Ismail-Meyer et al 2013;Ismail-Meyer 2014). The relatively good state of preservation of the plant remains and only limited presence of soil fauna excrements (mites) indicate a considerably high accumulation rate, rapid burial and generally waterlogged conditions (Fe/Mn ratio above 280 and Ca/Fe ratio above 1.5) of the deposit at the depth 109-110 cm b.g.l.…”
Section: Discussion: Sedimentological and Post-depositional Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…4A), with single fine charcoal fragments. It may represent the natural accumulation of organic material in the transition zone between the lake and land, but anthropogenic settlement activities, too, should be taken into account as a primary forming factor, as in the case of similar contexts (albeit with more numerous and differentiated anthropogenic inclusions) investigated at Lake Luokesa (Lithuania) and several Swiss lakeshore sites (Ismail-Meyer et al 2013;Ismail-Meyer 2014). The relatively good state of preservation of the plant remains and only limited presence of soil fauna excrements (mites) indicate a considerably high accumulation rate, rapid burial and generally waterlogged conditions (Fe/Mn ratio above 280 and Ca/Fe ratio above 1.5) of the deposit at the depth 109-110 cm b.g.l.…”
Section: Discussion: Sedimentological and Post-depositional Processesmentioning
confidence: 99%
“…4B, C), similar to material building the OSOM (see below). A combination of inland and littoral factors may have been responsible for the formation of the SOM: erosion of the upper sandy slopes of the kame and the resulting sedimentation of runoff downslope have to be considered (Ismail--Meyer et al 2013;Ismail-Meyer 2014). Also, the possibility that both the OM and SOM may have been (re)worked by episodic increases in the lake water level should be acknowledged, although no diatoms and only single sponge spicules were discovered.…”
Section: Discussion: Sedimentological and Post-depositional Processesmentioning
confidence: 99%
“…At L1, the proportion of plant remains represents over 50 % of the material throughout: in most cases it is composed of fragments of wood and bark, but twigs, leaves, fruits, seeds, charcoal and mosses are also present. Clay, sand and gravel are also documented (Pollmann 2014;Ismail-Meyer 2014). Much of this material was intentionally brought to the site as consumables, building and insulation material, produce from harvests and gathering, and bedding for livestock; much also reached the settlement accidentally.…”
Section: Discussionmentioning
confidence: 99%
“…After polymerization, they were cut into several sections with a diamond saw. To produce the 30 μm thin sections, the sections were cut into 47 × 47 mm blocks (Beckmann, 1997; Ismail‐Meyer, 2014). A total of 90 thin sections have been analysed from the 12 reference profile columns containing 225 macroscopically recognizable layers.…”
Section: Methodsmentioning
confidence: 99%
“…Simultaneously, dendrochronological analyses yielded exact dates for many settlements (e.g., Bleicher & Harb, 2015; Bleicher & Harb, 2017; Ebersbach, Ruckstuhl, & Bleicher, 2015; Harb & Bleicher, 2016; Jacomet, Leuzinger, & Schibler, 2004; Menotti & O'Sullivan, 2015; Menotti, 2012). Since the late 1970s, several sites have been analysed sedimentologically (e.g., Brochier, 1983; Joos, 1980) and in the 1990s, additional micromorphological analyses were adopted (e.g., Ismail‐Meyer, 2014; Ismail‐Meyer & Rentzel, 2004; Karkanas et al, 2011; Ostendorp, 1990; Pümpin, Wiemann, & Rentzel, 2015; Wallace, 1999). Pile‐dwelling research has shown that in this wet‐dry environment complex processes of preservation, degradation, reworking, and sedimentation occur.…”
Section: Introductionmentioning
confidence: 99%